Exploration of Hubula Counting System in Baliem Valley in Wamena Papua - Ronaldo Kho (FKIP Universitas Cenderawasih, 2023)
A number system is a system representing numbers. The study was ethnography research. This study explored the counting system Hubula communities use in their daily activities. There were three Hubula indigenous people as participants. Using in-depth interviews, observations, and documentation, the data was from Hubula’s indigenous people. The results of this study indicate that the order of numbers is only one to ten. The base numbers consist of one, two, and three, while the four to ten are repetitions of basic numbers. For naming the numbers five and ten, the Hubula communities use the expression of the finger-fold position, one hand for five and two hands for ten. They also recognize odd and even numbers. The odd number is one, three, five, seven, and nine, while the other is two, four, six, eight, and ten.